2016
DOI: 10.1080/09513590.2016.1241228
|View full text |Cite
|
Sign up to set email alerts
|

Lower placental growth factor and higher free β-hCG and PAPP-A levels in the fetal circulation of near-term pregnancies complicated with severe preeclampsia

Abstract: Lower PlGF and higher PAPP-A and free β-hCG levels were found in the fetal circulation of near-term severe preeclamptic pregnancies. There is a need for more research in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, several data from the literature would plaid in favor of a direct effect. Indeed, consistent with the present data, it has been recently showed that PLGF is detected in the fetal blood of human neonates [35]. In addition, VEGF-R1 is expressed by tip cells and relative levels of VEGF-R1 and VEGF-R2 contribute in tip cell position [21].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, several data from the literature would plaid in favor of a direct effect. Indeed, consistent with the present data, it has been recently showed that PLGF is detected in the fetal blood of human neonates [35]. In addition, VEGF-R1 is expressed by tip cells and relative levels of VEGF-R1 and VEGF-R2 contribute in tip cell position [21].…”
Section: Discussionsupporting
confidence: 90%
“…During pregnancy the umbilical cord blood contains PLGF [6, 35]. Our data show that in utero alcohol exposure impairs both the expression of brain VEGF-R1 and the radial organization of cortical microvessels, leading to speculation that PLGF can reach the fetal brain and contributes to alcohol-induced angiogenic impairments.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of studies on pro-angiogenic proteins in umbilical blood after pre-eclampsia and unaffected pregnancies are inconsistent [6,25]. In a recent study it was observed that median PlGF levels were lower in umbilical blood after pre-eclamptic pregnancy when compared with gestational age-matched controls [26], whereas Staff et al reported the same finding as ourselves, that in the majority of samples levels of PlGF were below the lowest concentration standard of the immunoassay kit [6]. In the study by Sezer et al it was found that there were no differences in sFlt-1 levels between a pre-eclampsia group and a control group as regards umbilical blood [26], as we reported, but there are also studies indicating that sFlt-1 concentrations are higher in umbilical blood after pre-eclampsia than after unaffected pregnancies [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of pregnancy, it can promote the growth of placenta, maintain, and guarantee pregnancy. 11 Altogether, hCG level may be involved in the pathogenesis of PE, but the mechanism behind the association is unclear. 10 Previous studies show that maternal serum hCG level of pregnancy with PE is significantly higher than that of the normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%